The price of democracy how money shapes politics and what to do about it - Cagé, Julia 1984- (Harvard University Press, 2020)
Introduction: Democratic exhaustion -- Part one. When the poor pay for the rich: The cost of democracy - first benchmarks -- The private funding of democracy - a system designed for the rich -- The realities of private funding - when the taxes of the many pay for the conservative preferences of the few -- Beyond politics - private funding of the "public good" -- Part two. Missed opportunities: A hope? Public funding of parties and election campaigns -- The public funding of democracy - a system in danger -- Are America's aberrations a danger for Europe? -- Let's save democracy! Reshaping political and social democracy -- Part three. The price of a vote - from local elections to general microtargeting: Has the last word been said? From the illusion of permanence to the novelty of democratic vouchers -- Towards a democratization of the "private" funding of democracy and a new way of publicly funding parties -- Towards a mixed assembly - social and political -- Conclusion: The prerequisites of "permanent" democracy.
Keywords: Repräsentative Demokratie; Demokratie; Politische Beteiligung; Soziale Ungleichheit; Parteienfinanzierung; Democracy; Representative government and representation